Sun-protective covers; Applied Solar Energy; Vol. 36, № 4 - Dyskin V. G. (2000, 2000)
It has been suggested to use composite materials as sun-protective and energy-saving covers for architectural glass. Magnetron sputtering provides reproducibility of properties, high productivity, and adhesive and mechanical strength in the industrial preparation of architectural glass. The technological advantages of magnetron sputtering of covers are due to the possibility of deposition of multiple covers in a single technological cycle. In addition, composite materials can be deposited by controlling the gas pressure and composition